The Dao in China’s Growing Presence in the South Pacific - Khasanah, Yulian Maulida; Rosyidin, Mohamad; Hanura, Marten (Global: Jurnal Politik Internasional, 2021)
The rise of China as one of the great powers in the international politic has been the hottest topic in the 21st century. Following the economic reform led by Deng Xiaoping in 1978, China re-emerges stronger than ever with its influences covering major parts of the world. One region particularly stands out since the prior dominance of United States therein, the South Pacific. The study of this research will be limited to 10 PICs recognising China, Vanuatu, Cook Island, FSM, Fiji, Niuee, PNG, Samoa, Tonga, Solomon Islands and Kiribati. Under the Western International Relations Theory (IRT) however, the rise of China is always seen in a rather malign manner. This research, therefore, contends that in order to fully understand China’s behaviour in the international community, we need to know how China perceives itself. By applying one of the most famous Chinese traditional school of thought, Daoism, this research aims to examine the strategy used in the expansion of China’s influence in the South Pacific. Daoism is symbolised with yin and yang, where the two elements are contradictory, yet they complement each other. Under the Dao dialectics, this research argues that China has been utilising a combination of two contradictory elements of power—soft and hard power—in expanding its prominence in the South Pacific region.